2020
DOI: 10.33448/rsd-v9i9.7433
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure decrease in elderly after isometric training: does lactate play a role?

Abstract: This study aimed to investigate the effect of isometric handgrip (IHG) training on the blood pressure (BP) reduction in prehypertensive and hypertensive elderly people, and the possible role of lactate and redox balance. Thirty-three older (75.3±1.3 years old) were allocated to a non-exercise control (CG, n=11), prehypertensive (PHG, n=10), and hypertensive (HG, n=12) groups. PHG and HG performed a total of 8 sets of 1-min bilateral contractions at 30% maximal voluntary isometric contraction, each separated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous studies have reported reductions in resting blood pressure following isometric handgrip training in individuals without hypertension and hypertensive individuals with and without antihypertensive medication compared to a control (Badrov, Bartol, et al, 2013; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Farah et al, 2018; Herrod et al, 2019; Millar et al, 2008, 2013; Ogbutor et al, 2019; Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Souza et al, 2020; Taylor et al, 2003). However, other randomized controlled trials have observed no reduction in any resting blood pressure assessments after isometric handgrip training compared to a control group in medicated Stage 2 hypertensive adults (Pagonas et al, 2017; Stiller‐Moldovan et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported reductions in resting blood pressure following isometric handgrip training in individuals without hypertension and hypertensive individuals with and without antihypertensive medication compared to a control (Badrov, Bartol, et al, 2013; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Farah et al, 2018; Herrod et al, 2019; Millar et al, 2008, 2013; Ogbutor et al, 2019; Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Souza et al, 2020; Taylor et al, 2003). However, other randomized controlled trials have observed no reduction in any resting blood pressure assessments after isometric handgrip training compared to a control group in medicated Stage 2 hypertensive adults (Pagonas et al, 2017; Stiller‐Moldovan et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐seven studies reported the chronic changes in resting blood pressure after isometric handgrip training (Ahmed et al, 2019; Allen et al, 2003; Alomari et al, 2010; Baddeley‐White et al, 2019; Badrov, Bartol, et al, 2013; Badrov, Horton, et al, 2013, 2016; Bank et al, 1998; Baross et al, 2017; Bentley et al, 2018; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Correia et al, 2020; Dempster et al, 2018; Dobrosielski et al, 2009; Farah et al, 2018; Gandhi, 2016; Garg et al, 2014; Goessler et al, 2018; Herrod et al, 2019; Hess et al, 2016; Howden et al, 2002; Lara et al, 2015; McGowan et al, 2006; McGowan, Levy, et al, 2007; McGowan, Visocchi, et al, 2007; Millar et al, 2007, 2008, 2013; Mortimer & McKune, 2011; Ogbutor et al, 2019; Okamoto et al, 2020; Pagonas et al, 2017; Peters et al, 2006, Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Saito et al, 2009; Sinoway et al, 1996; Somani et al, 2017, 2018; Somers et al, 1992; Souza et al, 2020; Stiller‐Moldovan et al, 2012; Taylor et al, 2003; Wiley et al, 1992; Yamagata & Sako, 2020; Zhang, 2003) (Table 2). In total, 22 studies included a nonexercise control group, three studies included a sham‐control group, one study provided a lifestyle modification program to both treatment and control groups, and 21 studies only had one or multiple isometric handgrip training groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30%–50% of maximal strength). Chronic training interventions, using low‐moderate intensity isometric handgrip exercise, have repeatedly observed reductions in resting blood pressure (Bentley et al, 2018; Jin et al, 2017; Kelley & Kelley, 2010; Loaiza‐Betancur & Chulvi‐Medrano, 2020; Souza et al, 2020). In contrast, there are only a few studies that have investigated the impact of isometric handgrip exercise on interference control.…”
Section: Introductionmentioning
confidence: 99%